A novel design for battery cooling based on highly thermally conductive phase change composites encapsulated by 3D printed polyethylene/boron nitride layer - Safna Nishad (16932474) (2025)
Lithium-ion batteries are vital in advancing the cell phone and automotive industry. However, their susceptibility to self-heating impacts their performance, service life, and safety. Thus, efficient thermal management devices are indispensable. Phase change materials (PCM) are increasingly studied for battery thermal management due to their passive thermal storage capacity and temperature homogeneity. However, challenges such as low thermal conductivity and PCM leakage during solid-liquid phase transition limit their applicability. This study presents a novel approach to address these issues by fabricating a highly conductive macro-encapsulated phase change composite. The composite is formed by infiltrating paraffin wax (PW) into graphite foam (GF) and encapsulating it with a polyethylene‑boron nitride (PE/BN) composite using 3D printing. The resulting encapsulated GF_PW composite demonstrates excellent thermal properties crucial for efficient battery cooling: thermal conductivity ranging from 4.5 to 4.6 W/m.°C and latent heat 129.5 to 153.1 J/g, respectively. A battery cooling pack (BCP), designed as a hollow cylindrical structure, effectively manages individual lithium-ion batteries' thermal performance without any PW leakage. Tests conducted at various discharge rates show that PCM-cooled batteries achieve significantly lower temperatures than those cooled by natural convection, with a notable temperature reduction of 11.3 °C at a discharge rate of 2.9C. The proposed BCP offers customization through paraffin waxes with varying melting points to adapt to different operational conditions, and its flexible fabrication technique accommodates batteries and battery modules of various sizes and shapes. Other Information Published in: Journal of Energy Storage License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.est.2025.115490